Peranan Notaris Dalam Perjanjian Kredit Perbankan Tentang Pinjaman Uang - Fitriyani Fitriyani; Ardi Muthahir (El-Ghiroh : Jurnal Studi Keislaman, 2021)
The existence of a notary as a service worker is given the authority by the State to make authentic deeds and then represents the State / government in the competence of private legal relations that occur in the midst of society. The existence of a notary in this matter really plays a role, including one in the bank credit agreement. The purpose of this study was to determine the role of a notary in bank credit agreements in the context of borrowing money. In addition, the role of the notary is also the authorized party to check goods.